Migration and union dissolution in a changing socio-economic context: The case of Russia - Hill Kulu; Magdalena Muszynska (Demographic Research, 2007)
Previous studies show that family migration is usually to the benefit of the man's professional career and that it has a negative impact on the woman's economic well-being and employment. This study extends previous research by examining the effect of family migration on union dissolution. We use the event-history data of two retrospective surveys from Russia and apply hazard regression. The analysis shows that couples who move frequently over long distances have a significantly higher risk of union dissolution than couples who do not move or move only once. Our further analysis reveals that the risk of disruption for frequent movers is high when the migrant woman has a job. Frequent migrants had a high risk of union dissolution during the Soviet period but they faced no such risk during the post-Soviet socio-economic transition. We argue that frequent moving increases union instability through a variety of mechanisms, the effect of which may vary across socio-economic contexts.